How to develop student creativity through teaching materials of hydrocarbon SETS-based? - F Hasanah; S Anwar (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to produce teaching materials of hydrocarbon SETS-based to develop student creativity through 4S TMD method. This article is the important part of the development of teaching materials that includes the selection and structuration steps. In the selection step, developing of indicators, explaining the concept of hydrocarbon using standardized textbooks sources, and developing student creativity and SETS aspects that can be integrated into hydrocarbon materials. Furthermore, in the structuration step, organizing concepts and materials into concept maps, macro structures, and multiple representations. The result of the two steps in the important part of this study produced a draft of SETS-based teaching material. Evaluation of the draft of teaching material has done by expert lecturers in the field of chemical education. The results show that the teaching material developed have been in conformity with the curriculum, scientifically correct, student creativity and SETS aspect is compatible with the subject matters, and concept maps, macro structures, multiple representations developed have been valid.